Estilos de vida en relación a actividad física y alimentación en los habitantes de la zona 15 de la ciudad de Loja, durante julio-diciembre del 2012 - Peña Alejandro, Carlos Andrés (2014)
The research project was descriptive, transversal and quantitative design approach in order to determine the physical and practical activity of eating habits as lifestyle components in the residents of the area 15 of the City of Loja in order to about your relationship with the presence of chronic diseases. To obtain validated test information on physical activity and eating habits was applied. The sample was taken from the total population of the area 15 of the Sucre parish, which is 134 inhabitants. The statistical program Epi Info 7 version 7.0.9.7 2012, and the results are represented in tables and graphics in Microsoft Office Excel 2011 program was evident was used for tabulation and analysis of physical activity of moderate or severe type associated a proper diet improved or type, has a beneficial effect to prevent the onset of chronic noncommunicable diseases.